Fluorescein-Guided Panendoscopy for Head and Neck Cancer Using Handheld Probe-Based Confocal Laser Endomicroscopy: A Pilot Study - Dittberner, Andreas; Ziadat, Rafat; Hoffmann, Franziska; Pertzborn, David; Gassler, Nikolaus; Guntinas-Lichius, Orlando (Frontiers in Oncology, 2021)
Background: White-light endoscopy and microscopy combined with histological analysis is currently the mainstay for intraprocedural tissue diagnosis during panendoscopy for head and neck cancer. However, taking biopsies leads to selection bias, ex vivo histopathology is time-consuming, and the advantages of in-vivo intraoperative decision making cannot be used. Confocal laser endomicroscopy (CLE) has the potential for a rapid and histological assessment in the head and neck operating room. Methods: Between July 2019 and January 2020, 13 patients (69% male, median age: 61 years) with newly diagnosed head and neck cancer (T3/T4: 46%) underwent fluorescein-guided panendoscopy. CLE was performed from both the tumor and margins followed by biopsies from the CLE spots. The biopsies were processed for histopathology. The CLE images were ex vivo classified blinded with a CLE cancer score (DOC score). The classification was compared to the histopathological results. Results: Median additional time for CLE during surgery was 9 minutes. 2,565 CLE images were taken (median CLE images: 178 per patient; 68 per biopsy; evaluable 87.5%). The concordance between histopathology and CLE images varied between the patients from 82.5% to 98.6%. The sensitivity, specificity, and accuracy to detect cancer using the classified CLE images was 87.5%, 80.0%, 84.6%, respectively. The positive and negative predictive values were 87.0% and 80.0%, respectively. Conclusion: CLE with a rigid handheld probe is easy and intuitive to handle during panendoscopy. As next step, the high accuracy of ex vivo CLE image classification for tumor tissue suggests the validation of CLE in vivo. This will evolve CLE as a complementary tool for in vivo intraoperative diagnosis during panendoscopy.